Technology for the creation of ferroelectric regular domain structures using interfering elastic waves - V. V. Krutov; A. S. Sigov (Российский технологический журнал)
Objectives. In many laboratories around the world, work is underway in the field of domain engineering of ferroelectrics. For a number of years, RTU MIREA has been conducting research on the creation of a high-performance technology for the formation of ferroelectric photonic and phononic crystals. The technology is characterized by a short duration of the technological cycle and provides the necessary depth of spatially periodic domain inversion. The key element of the technology is the combined effect of a uniform electric field and interfering high-frequency elastic waves that create a temperature grating. The technology is universal in relation to ferroelectrics of varying degrees of acoustic transparency, which is achieved by using highly dissipative liquid electrodes of a certain thickness. In this case, the energy of elastic waves practically does not penetrate into the ferroelectric, so the manifestation of undesirable effects is excluded. The purpose of this review article is to analyze the results of work carried out at RTU MIREA in the field of technology for the formation of ferroelectric regular domain structures (RDSs) during the period from 2008 to the present.Methods. Provisions of the theory of propagation, refraction and interference of elastic waves in condensed media are used, in particular, the Newtonian model of a liquid as applied to shear waves, as well as computer simulation. When considering the main stages of the Double Pulse heterothermal technology for the formation of RDSs, methods of analysis and synthesis were applied.Results. The possibility of forming not only micro-, but also submicron RDSs is shown. Recommendations are given on the choice of the type and specific properties of liquid electrodes, the angles between the direction of propagation of interfering waves, and their frequency. It is shown, in particular, that the use of highly dissipative ionic liquids as liquid electrodes creates favorable conditions for the formation of an RDS with a short period at room temperature. Thus, on shear waves with electrodes based on LiPF6-PC at a frequency of 300 MHz, RDS with a period of about 2 цт can be created. The main technological parameters are determined both for the case of the action of longitudinal elastic waves and for the case of shear waves with horizontal polarization. The results are applicable to ferroelectrics such as lithium niobate, potassium titanyl phosphate, and lead zirconate titanate.Conclusions. The proposed and studied methods are focused on the mass production of devices based on RDSs, in particular, on the manufacturing of optical parametric oscillators, acoustoelectronic devices, as well as terahertz wave generators and second harmonic oscillators. The technology has a short duration of the technological cycle, comparable to the polarization switching time in the used ferroelectric.